Gender and satisfaction of basic psychological needs: an exploratory study of pottery crafts in Latin America - Patricia S. Sánchez-Medina; René Díaz-Pichardo; Joseph S. Guevara-Flores (Entreciencias: Diálogos en la Sociedad del Conocimiento)
Purpose: This paper analyzes the relationship between gender and the satisfaction of basic psychological needs in the artisanal pottery sector in Latin America.